The Role of Innovation in Mediating Market Orientation to Company Performance - Putri, Putu Intan Paradictha Pradnya; Yasa, Ni Nyoman Kerti; Rahyuda, I Ketut (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2016)
The purpose of this study was to determine the effect of market orientation towards innovation, the effect of market orientation on performance, the effect of innovation on the performance and innovation mediating role of market orientation on corporate performance convection in Denpasar. This study took a sample of 123 respondents who market their products in the city of Denpasar. The analysis technique used in this study is the path analysis. Results of market orientation hypothesis testing showed positive and significant impact on innovation, market orientation and significant positive effect on company performance, innovation and significant positive effect on company performance. Innovation is able to mediate the relationship of market orientation on business performance significantly. The practical implications derived from this study that the orientation of the market is able to create innovations that will directly improve the performance of the company. Employers convection in Denpasar should develop a culture of orientation on the market so as to boost innovation by adapting new ideas oriented market changes in order to achieve improved performance of the company